Influência do processamento termomecânico em ciclos de deformação por trefilação e solubilização no desenvolvimento da mesotextura e nas propriedades mecânicas na superliga de níquel 718 - Azevedo, Luiz Maurício Barreto de (2019)
Superalloy 718 is a precipitation hardened nickel-based alloy. This alloy is commonly used for aerospace, nuclear and offshore industries because it maintains the mechanical properties almost unaltered from room temperature to 650°C. Iterative thermomechanical treatments are used to enhance the fraction of 3 n allied with refined microstructure and consequently mitigate intergranular defects without compromising mechanical properties. Nevertheless, researches in this area are made mainly using cold rolling deformation for plates. Therefore, the aim of this work is to study and propose an iterative thermomechanical route using wire-drawing and annealing heat treatment and verify if it is possible to achieve a CSL microstructure. For this goal, four routes were proposed with the same strain level followed by sub-solvus  and super-solvus  annealing heat treatment. The characterization of grain boundary distribution was performed by EBSD analysis. The  phase precipitation was observed by SEM and its quantification was performed by image analysis. Tensile tests at room temperature and hardness measurements were performed in order to evaluate the mechanical properties. The results show that, through processing route, was possible to achieve a high fraction of 3 n boundaries. The wire drawing induced a heterogeneous distribution of this boundaries.